2022
DOI: 10.1101/2022.06.15.22276447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ventilation Requirements and Recommendations for Controlling SARS-CoV-2 and Variants Outbreaks in Indoor Gathering Places with Close Contact

Abstract: Unexpected rapid infection involving SARS-CoV-2 variant Omicron known as the fifth wave of outbreak occurred since early January 2022 in Hong Kong. Almost 1.2 million citizens were infected in three months. Ventilation provisions in some gathering places with close contact such as restaurants were found to be lower than requirements, believed to be one of the main causes of transmission in these indoor spaces. At the end of the fifth outbreak in mid-May 2022, group infections were still found in several such g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nevertheless, when the probability of infection decreases from 1 to 0.1%, there is a corresponding requirement to raise the ventilation rate from 5.2 air changes per hour (ACH) to 52.4 ACH [64]. Based on Chow's outcomes [65], it can be inferred that in order to effectively manage the spread of COVID-19 throughout various buildings, it is necessary to maintain a minimum air exchange rate of six air changes per hour (ACH). The adoption of this particular value has shown its efficacy; nevertheless, it has also presented several problems.…”
Section: Mechanical Ventilation (Mv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, when the probability of infection decreases from 1 to 0.1%, there is a corresponding requirement to raise the ventilation rate from 5.2 air changes per hour (ACH) to 52.4 ACH [64]. Based on Chow's outcomes [65], it can be inferred that in order to effectively manage the spread of COVID-19 throughout various buildings, it is necessary to maintain a minimum air exchange rate of six air changes per hour (ACH). The adoption of this particular value has shown its efficacy; nevertheless, it has also presented several problems.…”
Section: Mechanical Ventilation (Mv)mentioning
confidence: 99%
“…Verifying if the ventilation system is intermittently deactivated for the sake of fuel conservation presents an additional level of complexity. The transmission of viruses may occur effortlessly [65]. A research indicated the use of mechanical ventilation with recirculation as a means to minimize ventilation costs.…”
Section: Mechanical Ventilation (Mv)mentioning
confidence: 99%
“…Rapid COVID-19 outbreaks of the fifth wave [1][2][3] in the Hong Kong Special Administrative Region (HKSAR) started from January 2022. This wave of outbreak is a quick incidence by a few incoming persons carrying the highly infectious Omicron variant infecting over 1.2 million citizens (over 16% of 7 million) in May 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate containment schemes have to be operated [4][5][6]. Catering services and public transport with inadequate ventilation or even with ventilation system turned off [7,8] should be watched. Healthcare systems handling testing, transportation, quarantine accommodation, medical treatment and temporary dead body storage are all overloaded.…”
Section: Introductionmentioning
confidence: 99%